Haematobiochemical and Histopathological Changes in Labeo rohita Infected with Aeromonas hydrophila by Immersion Challenge - MANOJ, C K; Mohanakumaran, C; Patel, M R; Salin, K R (Fishery Technology, 2025)
Haematobiochemical and histopathological variations in Labeo rohita subjected to immersion challenge with Aeromonas hydrophila by smearing a virulent bacterial culture (108 cfu/ml) over descaled portions (approximately 1cm2) near operculum and caudal peduncle of the fish were studied for a period of 15 days, with a view to assess the pathogenesis of the bacteria. The changes were recorded on 3rd, 5th, 7th, 10th and 15th days post infection (pi) and compared with a control and the results were compared statistically using Student’s t-test. The symptoms of the infected fish include sluggishness with pale red gills, liquefaction of the internal organs and marked blackening at the descaled areas. Tissue sections revealed dermal oedema and muscular degeneration focal hemorrhage and necrosis of liver necrotic changes of haematopoietic tissue, glomerulii and renal tubules in kidney hyperplasia of gill lamellae sloughing of intestinal mucosal epithelium and mild degenerative changes of myocardium. The total erythrocyte count (TEC) increased on 5th and 10th day post infection (pi) while haemoglobin (Hb) values decreased and total leucocyte count (TLC) increased during the period of study. Alkaline phosphatase (ALP), aspartate amino transferase (AST) and alanine amino transferase (ALT) activity of liver tissue were highest on 3rd day pi. There was no set pattern in the differential leucocyte count (DLC) between the infected and uninfected fish. Histological studies confirmed that the fishes exposed were infected with A. hydrophila and the variations recorded in the enzyme activities and cell counts of blood in the infected fish revealed their impaired health status, massive systemic damage and anaemia due to invasion of the bacteria.